Development of a PBL-Based e-Pocket Book with Mnemonic Strategies on Chemical Bonding Material Oriented Toward High School Students' Creative Thinking Abilities - Febrina, Putri; Rusdi, Muhammad; Haryanto, Haryanto; Afrida, Afrida; Romundza, Febbry (Yayasan Pendidikan Bima Berilmu, 2026)
Research has been conducted on the development of a PBL-Based e-Pocket Book learning media with Mnemonic Strategies on the topic of Chemical Bonds, oriented towards enhancing the Creative Thinking Skills of high school students. This study aims to assess the feasibility of the PBL-based e-pocket book with mnemonic strategies according to design and learning model experts, evaluate chemistry teachers' assessments, and understand students' responses to the developed media. This research uses the Lee & Owens development model. The research instruments include interview sheets and questionnaires. The developed product was validated by design and learning model experts as well as media and content experts, followed by an evaluation from chemistry teachers, and then tested through one-on-one trials and small group trials. The data analysis techniques used are qualitative data analysis and quantitative data analysis. The results indicate that the developed e-pocket book is deemed feasible based on the validation results from design and learning model experts, as well as media and content experts. The assessment from chemistry teachers also indicates a